Clinical Characteristics of Patients With Dizziness/Vertigo Accompanied by Posterior Semicircular Canal Hypofunction - Li, Zheyuan; Liu, Bo; Si, Hongli; Li, Kangzhi; Shen, Bo; Li, Xiang; Ling, Xia; Yang, Xu (Frontiers in Medicine, 2021)
Objective: To investigate the clinical characteristics of patients with dizziness/vertigo accompanied by loss of the posterior canal(s) (LPC). Methods: Clinical data of 23 patients with LPC were collected. We determined video-head-impulse test (vHIT) gains of all six semicircular canals and correlated vHIT findings with other vestibulo-cochlear tests, including caloric test, ocular and cervical vestibular-evoked myogenic potentials (oVEMP, cVEMP), pure tone audiometry (PTA), and analyzed the differences in clinical manifestations of patients with LPC with different etiologies. Results: LPC was identified in 23 patients. At the time of disease onset, most patients presented with dizziness (47.8%) and vertigo (30.4%), and some patients (21.7%) complained of unsteadiness. Among these 23 patients with LPC, there were 14 (60.9%) patients of isolated LPC (ILPC), 21 (91.3%) patients of unilateral LPC (ULPC) and 2 (8.7%) patients of bilateral LPC (BLPC). 1) Among 14 patients with ILPC, 13 (92.9%) patients had unilateral ILPC, the rate of ipsilesional impairment on caloric test, or oVEMP/ cVEMP test or PTA ipsilesionally was 53.8% (7/13). The causes of ILPC were vertigo/dizziness of unclear origin (38.5%), labyrinthine infarction (15.4%), vestibular migraine (15.4%) and other diseases (30.8%); 2) among 21 patients with ULPC, 7 patients (33.3%) were accompanied with horizontal semicircular canal hypofunction ipsilesionally, the abnormal rate of caloric test, or oVEMP/ cVEMP tests or PTA ipsilesionally was 57.1%. The causes of ULPC were vertigo/dizziness of unclear origin (33.3%), autoimmune inner ear disease (14.3%), labyrinthine infarction (14.3%), vestibular neuritis (9.5%), vestibular migraine (9.5%) and other diseases (19.0%); 3) among 2 patients with BLPC, one patient presented with unsteadiness, the causes of BLPC were vestibular paroxysmia and autoimmune inner ear disease. Conclusion: vHIT is a fast and effective method for assessing LPC, which can be used to detect isolated PC dysfunction. The causes of ILPC were peripheral origin or central origin. Patients with ILPC and ULPC mostly presented with dizziness /vertigo, and ULPC was often accompanied by ipsilateral vestibulo-cochlear impairment.